Experiences of Boosting Inpatient Exercise After HipFracture Surgery Using An Alternative Workforce - A Qualitative Study - Benny Lau; Marie K. March; Alison R. Harmer; Sarah Caruana; Christopher Mahony; Sarah Dennis (BMC Geriatrics, 2024)
Abstract Background Thrice-daily physiotherapy immediately following surgical repair of hip fracture has been shown to be safe and to reduce total hospital length of stay. However, implementing this is challenging with respect to health service funding and staffing. A novel approach may be to utilize an alternative workforce (allied health staff and student physiotherapists) to deliver two of the three daily treatments. However, how patients and staff may view such an approach is unknown. Thus, the aim of this qualitative study was to explore the views of inpatients with surgical repair of a hip fracture, their carers, health care professionals, and physiotherapy students about the implementation and acceptability of thrice-daily physiotherapy, with two sessions delivered by the alternative workforce (the BOOST study). Methods Semi-structured interviews and focus groups with patients, carers, health professionals and physiotherapy students. All interviews were digitally recorded and transcribed via verbatim. The transcripts were coded, and the data analysed via inductive thematic analysis. Results A total of 37 interviews (32 one-to-one interviews and five focus group interviews) were analysed. Five main themes were identified: (1) individual perceptions of the intervention: inpatients/carer/staff/student, (2) implementation within the service and organisational context, (3) implementation strategies that were effective, (4) improvements to implementation strategies/barriers to implementation/unsuccessful strategies and (5) future directions of BOOST. Conclusions The qualitative data revealed that higher frequency physiotherapy was well-received by inpatients and that staff/students involved in providing care perceived it as a safe, acceptable and valuable practice. Implementation of higher daily frequency of physiotherapy using an alternative workforce may feasibly be adopted for inpatients following hip fracture surgery. Trial registration This study was approved by the Human Research Ethics Committee (HREC) of the Western Sydney Local Health District (2020/ETH02718). Mutual recognition of approval was subsequently obtained from Northern Sydney Local Health District HREC.